Chronic cutaneous candidiasis in children: should we stop there? Report of two cases associated with auto-immune polyendocrinopathy syndrome type I - Basilice Mireille Minka; Aurélie Sibetcheu T; Suzanne Ngo Um Sap; Maryse Césarine Bissa (BMC, 2020)
Abstract Background Auto-immune polyendocrinopathy syndrome type I is a rare genetic disease, usually revealed by chronic superficial candidiasis and autoimmune endocrine dysfunction in childhood. Cases presentation We report the cases of 2 children, a 4 years-11 months old boy and 13 years old adolescent, admitted and followed up in the endocrinology unit of the Mother and Child Centre of Chantal Biya's Foundation for auto-immune polyendocrine syndrome type 1. Conclusion The occurrence of chronic cutaneous candidiasis in a child should always imply endocrine screening, to exclude auto-immune polyendocrine syndrome type I.